Maladies and Remedies for KVK trained Paddy Growers in Cuddalore District of Tamilnadu, India (Indian Journal of Extension Education, 2024)
KVK organizes a number of trainings related to paddy cultivation for improving the productivity and income of the paddy growers. To understand the maladies/constraints while attending the training and while adopting the KVK recommended technologies, the study was conducted in the Cuddalore District of Tamil Nadu in the year 2023. A list of trainees from the three bocks namely Srimushnam, Bhuvanagiri, & Vridhachalam of Cuddalore district were compiled with the assistance of the Krishi Vigyan Kendra (KVK). Using a simple random sampling technique, 150 respondents were selected from the three blocks. A well-structured interview schedule was utilized to gather data, tabulate the findings, and analyze the results. It was found that inadequate training duration (77.33%) followed by inadequate demonstrations (67.33%) while attending the KVK paddy related trainings. High input costs (85.33%), the non-availability of improved varieties (73.33%), were felt as major constraints while adoption of KVK recommended Paddy technologies. Providing low-cost inputs (88.67%), and timely distribution of inputs after training (80.00%) as suggestions given by the KVK-trained farmers. The constraints and suggestions expressed by the KVK Paddy farmers should be considered while organizing any paddy related training by the KVK system for further improving the adoption level of paddy growers.